(untitled) - Goetz, Stephan J. (London, 2005)
The production and consumption of land services is a complex subject involving economic, fiscal, social, psychological, health and environmental dimensions. This book documents the causes and effects of this.
Keywords: Land use,Agricultural conservation; Economic aspects; United states,Europe